KINERJA PEMERINTAH TERHADAP PENGELOLAAN SAMPAH DI KELURAHAN MACORAWALIE KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Sapri Sapri; Lukman Lukman; Citra Darwis; Herman Sanusi (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2021)
The purpose of this study is to determine the effect of Government Performance on Waste Management in Macorawalie Village, Panca Rijang District, Sidenreng Rappang Regency. The population in conducting this research is the community with male and female gender totaling 895 people from 2 hamlets, the data collection technique is the Yount formula with the results of 95 people, taken based on purposive sampling. The type of research used is quantitative descriptive research type, data collection techniques used are observation, questionnaires, and interviews. The data analysis technique is using validity, reliability using SPSS 16.0 application and Likert Scale. Based on the results obtained from the questionnaire analysis, a recapitulation of Government Performance variables obtained 67.6% is included in the